Face-to-Face and Virtual Academic Writing Tutoring Sessions: What Can Be Learnt from their Didactic Strategies? - Núñez Cortés, Juan Antonio; Errázuriz, María Constanza; Neubauer Esteban, Adrián; Parada, Claudia (Íkala, Revista de Lenguaje y Cultura, 2021)
In Spanish-speaking settings, newly-emerged writing tutoring centers have seen the need to adapt to emergency remote education due to the health emergency brought about by covid-19. However, there is lack of evidence regarding how writing tutoring actually works under this education modality. Drawing on the above, this article aimed to analyse the didactic strategies used by two peer tutors in both face-to-face writing tutoring sessions that occurred before the pandemic and online sessions taking place during the pandemic, after having undergone a specific training program. Data were collected through a quantitative-qualitative approach, and the maxqda software was used to do a content analysis of 16 tutoring session (8 face-to-face and 8 online) transcriptions. Findings show a prevalence of cognitive approaches, mainly questioning; along with instructional approaches, such as suggestion and explanation. Nonetheless, differences are perceived between the various types of tutoring sessions, along with a trend toward a more student-centered approach in online tutoring sessions. These results suggest online tutoring sessions are a useful alternative when accompanying the writing process in university students.